Women's entrepreneurship, neoliberalism and economic justice in the postfeminist era: A discourse analysis of policy change in Sweden. Issue 5 (16th July 2018) - Berglund, Karin; Ahl, Helene; Pettersson, Katarina; Tillmar, Malin
Abstract : Since the early 1990s, there has been investment in women's entrepreneurship policy (WEP) in Sweden, which continued until 2015. During the same period, Sweden assumed neoliberal policies that profoundly changed the position of women within the world of work and business. The goals for WEP changed as a result, from entrepreneurship as a way to create a more equal society, to the goal of unleashing women's entrepreneurial potential so they can contribute to economic growth. To better understand this shift we approach WEP as a neoliberal governmentality which offers women 'entrepreneurial' or 'postfeminist' subject positions. The analysis is inspired by political theorist Nancy Fraser who theorized the change as the displacement of socioeconomic redistribution in favour of cultural recognition, or identity politics. We use Fraser's concepts in a discourse analysis of Swedish WEP over two decades, identifying two distinct discourses and three discursive displacements. Whilst WEP initially gave precedence to a radical feminist discourse that called for women's collective action, this was replaced by a postfeminist neoliberal discourse that encouraged individual women to assume an entrepreneurial persona, start their own business, compete in the marketplace and contribute to economic growth. The result was the continued subordination of women business owners, but it also obscured or rendered structural problems/solutions, and collective feminist action, irrelevant.